Non-invasive ventilation during paediatric retrieval: a systematised review - Cheema, Baljit Kaur (Division of Emergency Medicine, 2018)
Background: In hospital critical-care and emergency settings, non-Invasive ventilation (NIV) is increasingly used in neonatal and paediatric patients as an alternative to invasive positive pressure ventilation (IPPV). Critically ill children and babies may need transfer to higher levels of care, but the emergency transport setting is lagging behind the hospital sector in terms of availability of NIV. Aim and objectives: The goal of this study was to assess the evidence on the safety and effectiveness of NIV in children during transportation. Safety outcome measures were intubation or escalation of ventilation mode (during and soon after transport) and adverse event (AE) occurrence during transport. Effectiveness outcome measures related to improvement in clinical parameters during transfer. Methods: A systematised review of the literature was conducted, based on searches of MEDLINE via PubMed, EMBASE (via Scopus), Cochrane Central Register of Controlled Trials (CENTRAL), African Index Medicus, Web of Science Citation Index and the World Health Organisation Trials Registry (ICTRP). Two reviewers independently reviewed all identified studies for eligibility, with an initial screening round followed by a full-text review of potentially relevant articles. The quality of studies meeting inclusion criteria was evaluated using an adapted quality assessment tool developed for this study. Results: A total of 1287 records were identified; of these, 12 studies met inclusion criteria. Following quality assessment, eight studies were included and four studies were excluded. There were no randomised controlled trials, quasi-randomised controlled trials or non-randomised studies of intervention, to answer the research question. The included studies were all observational in design: seven studies (n= 708) evaluated in-transport use of continuous positive airway pressure (CPAP) and one study (n=150) reported on use of high-flow nasal cannula (HFNC) in children during transport. During transport on NIV, 3/858 (0.4%) patients required either intubation (1/708; 0.1%; CPAP studies) or escalation of mode of ventilation (2/150; 1%; HFNC study). In the 24 hours following transfer, 63/650 (13%) of children transferred on NIV, were intubated. The odds of intubation within 24 hours were significantly higher for CPAP transfer 60/500 (12%) compared with HFNC 3/150(2%): OR (95% CI) 6.68 (2.40 - 18.63), p=0.00003. Adverse events, where reported, were found to occur in 2-4% of NIV transports, with use of BVM in 8/334 (2%), desaturation episodes in 9/290 (3%), apnoea in 11/290(4%) and administration of CPR in 0/290 (0%) cases being described. There was insufficient reporting of change in vital signs or clinical condition during transport for meaningful analysis. Conclusion: This study is the first systematised review indicating that NIV use in children during transport is likely to be safe. From the low-reliability evidence available, it was calculated that NIV use in children during transport would result in a 0.4% rate of intubation or escalation during transport and an in-transport adverse event rate of 2-4%. There was insufficient evidence to comment on clinical effectiveness of NIV during transfer. Following NIV transfer, 13% of patients were intubated within 24 hours, with significantly higher odds of intubation in children transported on CPAP compared with HFNC. Recommendations: Further research is needed in order to make firm recommendations regarding the safety and effectiveness of NIV during transport of children. A recommended minimum data set, for the standardised reporting of observational studies of paediatric NIV use during transport, is suggested. It is recommended that transport databases and registries are expanded to include NIV details as well as information regarding the presence or absence of pre-specified adverse events during transport.